Links Between Parenting and Internalizing and Externalizing Problems: Cross-Cultural Evidence from Ten Countries - Vazsonyi, Alexander T; Ksinan, Albert J; Javakhishvili, Magda; Scarpate, J Melissa; Kahumoku-Fessler, Emily (Child psychiatry and human development, 2022)
The present study tested the links between perceived maternal and paternal parenting and internalizing and externalizing problems across ten cultures (China, Czech Republic, Hungary, the Netherlands, Slovenia, Spain, Switzerland, Taiwan, Turkey, and the United States). Self-report data were collected from N = 12,757 adolescents (Mage = 17.13 years, 48.4% female). Multigroup confirmatory factor analyses and structural equation models tested whether: (1) the six parenting processes (closeness, support, monitoring, communication, peer approval, and conflict; Adolescent Family Process, Short Form (AFP-SF, 18 items) varied across cultures, and (2) the links between parenting processes and measures of internalizing and externalizing problems varied across cultures. Study findings indicated measurement invariance (configural and metric) of both maternal and paternal parenting processes and that the parenting-internalizing/externalizing problems links did not vary across cultures. Findings underscore the ubiquitous importance of parenting processes for internalizing and externalizing problems across diverse Asian, European, Eurasian, and North American cultures.
Keywords: rodičovství; průzkumy a dotazníky; Female; srovnání kultur; ženské pohlaví; Peer Group; Surveys and Questionnaires; Adolescent; lidé; Parenting; otcové; vyrovnaná skupina; Spojené státy americké; Male; Cross-Cultural Comparison; United States; Fathers; mužské pohlaví; mladiství; Humans